Implementasi Ice Breaking Terhadap Penguatan Konsentrasi Peserta Didik Pada Pembelajaran Tematik - Nazhifah, Salsabila; Budianto; Fathulloh (STAI AL-AMIN, 2024)
Ice Breaking is a game or activity that functions to change the atmosphere of ice in a group. The 2013 curriculum is expected to provide a balanced balance of cognitive aspects, affective aspects and psychomotor aspects, so that the learning that occurs is expected to run by balancing these three aspects, unlike what has happened so far where learning tends to prioritize only cognitive aspects. If icebreaking is used in 2013 curriculum learning, it will be fun learning and strengthen students' concentration. In this research, researchers used a qualitative approach with qualitative descriptive methods. The data in this research was obtained through interviews, observation and documentation. The results of this research relate to the application of icebreaking to increase students' concentration in thematic learning. The process of implementing icebreaking in class VI thematic learning has gone well, starting from selecting the types of quizzes and games to be implemented. The positive impact is that students are happy and can interact with other students, apart from that, students are trained to concentrate on the icebreakers given, students become more familiar with other friends, and appreciate friends' answers even though they are wrong, and students are also invited to to solve the problem of a given icebreaker.